(untitled) (Third Sector Social Economic Review, 2025)
The transportation sector is one of the sectors negatively affected by the COVID-19 Pandemic. In the transportation sector, passenger transportation is one of the sectors most affected by the pandemic. While the share of airline passenger transportation in the overall transportation sector may not be very high, it plays a crucial role in spreading the pandemic due to its extensive use in international travel. Airline passenger transportation, holding a substantial market share in the passenger transportation sector, was also adversely affected by the pandemic. This paper investigated the pandemic’s impact by comparing airlines’ financial performance before and after the pandemic. According to Skytrax, the study focused on 2019-2022 annual data for the seven best airlines in Europe. Unlike earlier studies, this study compared DuPont and MABAC analysis to evaluate the financial performance of the airlines. Microsoft Excel analyzed net profit/ loss, revenue, total assets, current liabilities, non-current liabilities, total liabilities and equity, and total equity data. Return on Sales (ROS), Asset Turnover, ROA (Return on Assets), equity multiplier, and ROE (Return on Equity) values were used in DuPont and MABAC analysis. The results show that KLM (2019, 2020, and 2022) and Turkish Airlines (2021) are the best in Europe because of their financial performance.